Heterologous prime-boost vaccination with VLA2001 and an ORFV-based vector enhances spike- and nucleocapsid-specific immunity in mice - Reguzova, Alena; Haug, Verena; Metz, Carina; Müller, Melanie; Fandrich, Madeleine; Dulovic, Alex; Amann, Ralf (Frontiers in Immunology, 2025)
Heterologous prime–boost vaccination has emerged as a promising approach to enhance immune responses by combining vaccines with complementary mechanisms of antigen delivery and immune activation. Here, we evaluated the immunogenicity of heterologous regimens combining the licensed inactivated SARS-CoV-2 vaccine (VLA2001) with the replication-deficient Orf virus-based vector vaccine (Prime-2-CoV). Using a mouse model, we compared these regimens to homologous vaccinations with each vaccine alone. Among the combinations tested, priming with VLA2001 followed by boosting with Prime-2-CoV induced the strongest spike-specific antibody responses, superior ACE2-binding inhibition against pre-Omicron variants, and robust Th1-biased immunity, with robust CD4+ and CD8+ T-cell responses. This sequence also enhanced nucleocapsid-specific immunity, underscoring the benefit of multiantigen targeting. These findings highlight the immunological synergy between inactivated whole-virus and ORFV vector vaccines and support the strategic use of Prime-2-CoV as a potent heterologous booster. The ORFV platform’s favorable safety profile and Th1-polarizing capacity make it a valuable candidate for future heterologous vaccine strategies beyond SARS-CoV-2.